Assessment of reaction intermediates of gamma radiation-induced degradation of ofloxacin in aqueous solution. (October 2018) - Changotra, Rahil; Guin, Jhimli Paul; Varshney, Lalit; Dhir, Amit
Abstract: Gamma radiolytic degradation of an antibiotic, ofloxacin (OFX) was investigated under different experimental conditions. The parameters such as initial OFX concentration, solution pH, absorbed dose and the concentrations of inorganic ( CO 3 2 − ) and organic ( t -BuOH) additives were optimized to achieve the efficient degradation of OFX. The degradation dose constant values of OFX were calculated as 2.364, 1.159, 0.776 and 0.618 kGy −1 for the initial OFX concentrations of 0.05, 0.1, 0.15 and 0.2 mM with their corresponding (G (-OFX)) values of 0.481, 0.684, 1.755 and 1.971, respectively. Degradation rate of OFX was significantly increased with increase in the absorbed dose and decrease in the initial OFX concentration under acidic condition when compared to neutral or alkaline condition. Reaction of OFX in the presence of CO 3 2 − and t -BuOH showed that the degradation was primarily caused by the reaction of OFX with radiolytically generated reactive hydroxyl radicals. Mineralization extent of OFX was determined in terms of percentage reduction in total organic carbon (TOC) and results revealed that the addition of H2 O2 enhanced the mineralization of OFX from 29% to 36.1% with H2 O2 dose of 0.5 mM at an absorbed dose of 3.0 kGy. Based on the LC-QTOF-MS analysis, gamma radiolytic degradation intermediates/products of OFX were identified and the possible degradation pathways of OFX were proposed. Cytotoxicity study of the irradiated OFX solutions showed that gamma radiation has potential to detoxify OFX. Highlights: Ofloxacin could be completely degraded with gamma radiation. The radiolytic degradation of ofloxacin followed pseudo-first-order kinetics model. Radiation chemical yield, dose constants, and absorbed dose for 50 and 90% degradation are discussed. The transformed products (TPs) of antibiotic oflaxacin were identified and proposed pathways for TPs were suggested.